2010
DOI: 10.1095/biolreprod.109.083360
|View full text |Cite
|
Sign up to set email alerts
|

Progestin Exposure Before Gonadotropin Stimulation Improves Embryo Development after In Vitro Fertilization in the Domestic Cat1

Abstract: This study investigated the influence of progestin priming and ovarian quiescence on response to exogenous gonadotropin stimulation in the cat. Because a subpopulation of cats routinely ovulated spontaneously, there also was the opportunity to examine the ovary's reaction to the added impact of endogenously secreted progestagen. Queens were given 1) equine chorionic gonadotropin (eCG) plus human chorionic gonadotropin (hCG) only (control; n ¼ 9 cats), 2) GnRH antagonist (antide) injections followed by eCG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…In fact, this mechanism is not completely clear even for the domestic cat, although it has been shown that ovarian quiescence alone is not sufficient to enhance follicular responses to gonadotropins [14]. On the other hand, when quiescence is achieved by synthetic progestin exposure before treatment with gonadotropins, the ovaries appeared to respond more uniformly after ovulation induction, producing higherquality oocytes from more viable follicles in domestic cats [30]. These authors suggested a possible mechanism might include progestin actions at both the organ and cellular level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, this mechanism is not completely clear even for the domestic cat, although it has been shown that ovarian quiescence alone is not sufficient to enhance follicular responses to gonadotropins [14]. On the other hand, when quiescence is achieved by synthetic progestin exposure before treatment with gonadotropins, the ovaries appeared to respond more uniformly after ovulation induction, producing higherquality oocytes from more viable follicles in domestic cats [30]. These authors suggested a possible mechanism might include progestin actions at both the organ and cellular level.…”
Section: Discussionmentioning
confidence: 99%
“…On the ovary, progestins might promote a more efficient recruitment and growth of high-quality oocytes and reduce atresia of antral follicles, assigning a higher number of gonadotropin-receptive follicles [29,30]. At the cellular level, enhancements in follicular granulosa cell gonadotropin receptor populations, whether by increased numbers or enhanced sensitivity, could explain the improved responses to gonadotropins of females previously treated with progestins [29,30]. Further studies are needed to determine if one or both of these mechanisms function in ovarian responses to progestin pretreatment in felids, including in southern tigrinas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COCs from antral (O2 mm diameter) follicles were harvested 24 h post-hCG by laparoscopic aspiration according to our earlier descriptions (Pelican et al 2010). Recovery medium consisted of HEPES-buffered modified Ham's F10 (Irvine Scientific, Santa Ana, CA, USA) supplemented with 2 mmol/l L-glutamine, 1 mmol/l pyruvate, 100 IU/ml penicillin, 100 mg/ml streptomycin, 0.37 mg/ml heparin (sodium salt Grade 1A), and 4 mg/ml BSA (A9418; Pelican et al 2010, Crosier et al 2011. COCs with an expanded cumulus cell mass were rinsed in nonheparinized collection medium.…”
Section: Collection Of Preovulatory Cocsmentioning
confidence: 99%
“…Oocytes were inseminated with conspecific spermatozoa collected, evaluated, and cryopreserved from two colony donors as described previously (Howard et al 1993, Pukazhenthi et al 1999. A 10 ml aliquot of 2!10 6 thawed and motile spermatozoa per milliliter was added to each 40 ml insemination drop (Spindler & Wildt 1999, Comizzoli et al 2003, Spindler et al 2006, Pelican et al 2010. To control for parthenogenetic activation, some drops were shaminseminated using 10 ml of sperm-free insemination medium (Comizzoli et al 2004).…”
Section: Insemination Of Oocytes and Culture Of Embryos In Vitromentioning
confidence: 99%